The therapeutic potential of exercise for improving mobility in multiple sclerosis - Locatelli, Giuseppe; Stangel, Martin; Rooks, Daniel; Boesch, Julian; Pierrel, Eliane; Summermatter, Serge (Frontiers in Physiology, 2024)
Multiple sclerosis (MS) is a chronic autoimmune disease characterized by inflammation and demyelination in the central nervous system (CNS) with subsequent axonal and neuronal degeneration. These changes are associated with a broad range of symptoms including skeletal muscle dysfunction. Importantly, musculoskeletal impairments manifest in various ways, compromise the quality of life and often precede the later development of mobility disability. As current standard disease modifying therapies for MS predominantly act on neuroinflammation, practitioners and patients face an unmet medical need for adjunct therapies specifically targeting skeletal muscle function. This review is intended to detail the nature of the skeletal muscle dysfunctions common in people with MS (pwMS), describe underlying intramuscular alterations and outline evidence-based therapeutic approaches. Particularly, we discuss the emerging role of aerobic and resistance exercise for reducing the perception of fatigue and increasing muscle strength in pwMS. By integrating the most recent literature, we conclude that both exercise interventions should ideally be implemented as early as possible as they can address MS-specific muscle impairments. Aerobic exercise is particularly beneficial for pwMS suffering from fatigue and metabolic impairments, while resistance training efficiently counters muscle weakness and improves the perception of fatigue. Thus, these lifestyle interventions or possible pharmacological mimetics have the potential for improving the general well-being and delaying the functional declines that are relevant to mobility.